Type 2 diabetes complications and comorbidity in Sub-Saharan Africans - Kenneth Ekoru (EClinicalMedicine, 2019)
Background: Context-specific evidence of the spectrum of type 2 diabetes (T2D) burden is essential for setting priorities and designing interventions to reduce associated morbidity and mortality. However, there are currently limited data on the burden of T2D complications and comorbidity in sub-Saharan Africa (SSA). Methods: T2D complications and comorbidities were assessed in 2,784 participants with diabetes enrolled from tertiary health centres and contextualised in 3,209 individuals without diabetes in Nigeria, Ghana and Kenya. T2D complications and comorbidities evaluated included cardiometabolic, ocular, neurological and renal characteristics. Findings: The most common complications/comorbidities among the T2D participants were hypertension (71%; 95% CI 69–73), hyperlipidaemia (34%; 95% CI 32–36), and obesity (27%; 95% CI 25–29). Additionally, the prevalence of cataracts was 32% (95% CI 30–35), diabetic retinopathy 15% (95% CI 13–17), impaired renal function 13% (95% CI 12–15), and erectile dysfunction (in men) 35% (95% CI 32–38). T2D population-attributable fraction for these comorbidities ranged between 6 and 64%. Interpretation: The burden of diabetes complications and comorbidity is substantial in SSA highlighting the urgent need for innovative public health strategies that prioritise promotion of healthy lifestyles for prevention and early detection of T2D. Also needed are strategies to strengthen health care system capacities to provide treatment and care for diabetes complications. Keywords: Type 2 Diabetes, Sub-Sahara Africa, Complications, Co-morbidity, Epidemiology